The Study of Fear Comminication and its Compare in Tehran Islamic - Nasrollah, Sepideh; Sahbaie, Faezeh; Seifi, Bahar; Zare, Mohammad (Advances in Nursing & Midwifery, 2015)
communication is associated with fear of negative evaluation, decreased social activities and low self-esteem. Fear of communication is the fourth most prevalent psychiatric disorders in Iran, as elsewhere, is highly prevalent among adolescents. Since communication apprehension have a significant negative impact on students' performance detection, diagnosis and early intervention t can be helpful. The aim of this study was to determine the Fear of communication among medical and nursing students of Islamic Azad University of Medical Sciences, Tehra, Irann. Method and materials: This study was a descriptive comparative study .The sample of the study consisted of 500 students of Islamic Azad University, Tehran Medical Branch participated. Participants were included in the study by cluster sampling method. Half of the students were sophomores and the other half were thirdyear students in the Faculty of Medicine and Nursing. Data were collected by a questionnaire which consisted of demographic information, and (PRCA) 24, a twenty-four statements concerning feelings about communication with others. Results: Most of the participants in the second year, were medical students and most of the third year students were nursing students. The results showed that the most prevalent fear in second year and third year students associated with frightening situations (group discussion, presentation, interpersonal, public speaking) .The scores of fear of communication were higher in second year students comparing to third year students. Remarkably, a significant relationship between demographic characteristics such as the field of education, occupation, marital status, parental education, parental occupation and family size were obtained in both groups (P< 0.05). Conclusion: There is a need for early identification of the disorder providing information and education for students and their parents. Keywords: Fear of communication, communication apprehension, Nursing students, Medical students.